Implementasi Pembelajaran Tahfidzul Qur’an dengan Metode Ma’ani di Pesantren Darussalam Bone - Sugiyanto Sam; Nurul Hikmah (TAUJIH: Jurnal Pendidikan Islam, 2025)
This study aims to examine the application of the Ma’ani method in the Tahfidzul Qur’an program at the Darussalam Bone Islamic Boarding School. The Ma’ani method is an innovative approach that integrates memorization of the Qur'an with an understanding of the meaning and context of its verses. This approach not only helps students memorize the Qur'an but also provides a deep understanding of the mufradat, Arabic language structure, and the messages contained in the verses of the Qur'an. This method is used as a strategic step to increase students' interest in studying Islamic knowledge, including yellow books, in a relevant and applicable manner. The research employed a descriptive qualitative method with a field research approach. Data were collected through direct observation at the research site and in-depth interviews with teachers. Observation techniques were also used to understand the actual patterns of application of the method. Data analysis was conducted thematically to identify patterns, strengths, and challenges encountered in implementing the Ma’ani method. The results of the study show that the results of the study show that the implementation of the Ma’ani method is driven by four main reasons, namely fulfilling parental expectations, increasing students' interest in studying the yellow book, guiding students to find life solutions through understanding verses, and providing new alternatives in the tahfidz method. The implementation process includes tahsin, giving memorization targets, vocabulary and meaning talqin, tadabbur, tiered muraja'ah, 1 juz memorization deposit, and tasmi'.